Kemakbulan Doa dalam Perspektif Al-Qur'an dan Fisika Gelombang - Qowiyyah, Siti Naashirotul (Qaf: Jurnal Ilmu Al-Qur'an dan Tafsir, 2022)
Prayer is a request that is said by the servant with hope and humility to Him to get what he wants. Allah SWT is the One Who Answers Requests, Allah SWT tells us to pray not because He needs something from us. We pray or not, obey or disobey, the majesty and glory of Allah SWT remains perfect and cannot be reduced. His glory does not decrease because we disobey, nor does His glory increase because we obey Him. This article uses a qualitative research approach where the type of research is library research. The data collection technique uses documentation methods and data sources obtained from primary data, namely the Qur'an and secondary data, namely prayer epistemology books, destiny changing prayer books, and other works related to the source of the discussion. The results showed that prayer in the view of science in the nature of waves, namely first, the wave is reflected (reflection) that Allah SWT accepts and grants our prayers. Second, the wave is refracted (bending) between actions and words that are not commensurate so that it can hinder the approval of our prayers. Third, the waves are combined like praying with behavior or actions that are in accordance with the ethics and procedures of praying, thus ensuring the fulfillment of the desired needs. Then the essence of prayer is the integration of general knowledge with religious knowledge (the Qur'an).